Model-based hardware in the loop control of collaborative robots - Safeea, Mohammad (2020)
Simulation and model-based design software packages are widely used in many engineering disciplines. When it comes to robotics those tools are very important for robot design, simulation and the development of control algorithms before the implementation on the real robot. Simulink by MathWorksR is an advanced model-based design tool. It is popular in education, industry and research. In addition, Simulink supports several hardware components, facilitating a rapid deployment of the developed programs on the target hardware. In this study, the SimulinkIIWA interface for controlling KUKA iiwa robots from Simulink is presented and compared to the KUKA Sunrise Toolbox (KST). This interface is based on the User Datagram Protocol (UDP) and allows graphical real-time control of iiwa robots from Simulink without a need for writing any code. The interface supports different robot control modes, at the joints level and at the end-effector (EEF) level. Example applications are also provided showing the flexibility and the ease of use of the proposed interface